Spontaneous bacterial peritonitis due to Listeria monocytogenes: importance of enrichment culture. Issue 9 (29th July 2010) - Jayasinghe, Saroj; Connor, Martin; Donaldson, Shona; Austin, Hannah; Foster, Adele
Abstract : A case of Listeria monocytogenes induced spontaneous bacterial peritonitis (SBP) is reported in a patient with primary biliary cirrhosis. It is an indolent illness and may not show a neutrophil reaction in peritoneal fluid. Enrichment broth was required to isolate L monocytogenes in the patient. This is not routinely used in the UK and therefore isolates may be missed. L monocytogenes remains sensitive to ampicillin, penicillin and gentamicin, but is resistant to cephalosporin antibiotics. The rising incidence of listeriosis in the population suggests that the incidence of SBP from L monocytogenes is likely to increase.